Еthnolinguistic position of proverbs-saying related to money in the Kazakh and Turkish languages - Sabasova, G. A. (Journal of Oriental Studies, 2016)
In given article the nature from an ethnolinguistic position connected with money reveals, i.e. with richness, the basic sources ofrichness (gold, tenge, tiyin, fels, etc.) proverbs-sayings in the Kazakh and Turkish languages, are considered their difference and similarityamong themselves.